2020
DOI: 10.5604/01.3001.0014.6054
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Associated Factors in Latin American Patients Undergoing Total Hip Arthroplasty

Abstract: Background. The objective of this study was to determine whether individuals with hip osteoarthritis who undergo THA have higher HRQOL scores than those awaiting the procedure; An additional aim was to investigate associated factors exerting an impact on HRQOL. Materials and methods. A cross-sectional study was conducted. Participants were divided into two groups: pre-THA and post-THA. Functional capacity was assessed using the Harris Hip Score, and HRQOL was measured using a validated and adapted version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In previous research, frail patients with OA had more adverse events in daily activities after THA and TKA; consequently, they had an increased dependence on outside help, and a decrease in IADL and HRQoL. 32 , 33 Reportedlly, total joint arthroplasty for hip and knee OA is highly effective in relieving pain and improving physical function, 7 , 34 , 35 which is supported by our findings showing significant improvement in pain, IADL, and HRQoL at 6 months after surgery. We also found that frailty in patients was significantly decreased from 57.4 to 38.2% by THA and TKA procedures.…”
Section: Discussionmentioning
confidence: 98%
“…In previous research, frail patients with OA had more adverse events in daily activities after THA and TKA; consequently, they had an increased dependence on outside help, and a decrease in IADL and HRQoL. 32 , 33 Reportedlly, total joint arthroplasty for hip and knee OA is highly effective in relieving pain and improving physical function, 7 , 34 , 35 which is supported by our findings showing significant improvement in pain, IADL, and HRQoL at 6 months after surgery. We also found that frailty in patients was significantly decreased from 57.4 to 38.2% by THA and TKA procedures.…”
Section: Discussionmentioning
confidence: 98%